2023
DOI: 10.1186/s12934-023-02117-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving therapeutic protein secretion in the probiotic yeast Saccharomyces boulardii using a multifactorial engineering approach

Abstract: The probiotic yeast Saccharomyces boulardii (Sb) is a promising chassis to deliver therapeutic proteins to the gut due to Sb’s innate therapeutic properties, resistance to phage and antibiotics, and high protein secretion capacity. To maintain therapeutic efficacy in the context of challenges such as washout, low rates of diffusion, weak target binding, and/or high rates of proteolysis, it is desirable to engineer Sb strains with enhanced levels of protein secretion. In this work, we explored genetic modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Earlier reports on engineered probiotics have highlighted the importance of maintaining the genetic stability of the heterologous protein encoding genes during bacterial growth (Landry and Tabor, 2018). Although, the most preferred route to achieve genetic stability is to integrate the heterologous genes in the chassis genome, studies have shown that this could significantly reduce the overall production (Aggarwal et al, 2020) and secretion (Durmusoglu et al, 2023) levels of recombinant proteins. As in our case, we were unable to observe darobactin production in the liquid cultures, using a medium-copy vector backbone (p15A ori), we decided not to proceed with genomic integration approaches for our genetic circuits.…”
Section: Selection Of An Efficient Antibiotic Supplementation-free Pl...mentioning
confidence: 99%
“…Earlier reports on engineered probiotics have highlighted the importance of maintaining the genetic stability of the heterologous protein encoding genes during bacterial growth (Landry and Tabor, 2018). Although, the most preferred route to achieve genetic stability is to integrate the heterologous genes in the chassis genome, studies have shown that this could significantly reduce the overall production (Aggarwal et al, 2020) and secretion (Durmusoglu et al, 2023) levels of recombinant proteins. As in our case, we were unable to observe darobactin production in the liquid cultures, using a medium-copy vector backbone (p15A ori), we decided not to proceed with genomic integration approaches for our genetic circuits.…”
Section: Selection Of An Efficient Antibiotic Supplementation-free Pl...mentioning
confidence: 99%
“…Saccharomyces boulardii (S. boulardii or Sb ) is a probiotic yeast that was first isolated from lychee and mangosteen by Henri Boulard in 1923. , Compared to Saccharomyces cerevisiae (with which it shares 99% genomic relatedness), Sb can better tolerate low pH and human body temperature, enabling improved survival in the human gut. Sb is currently used to treat ulcerative colitis, diarrhea, and recurrent Clostridium difficile infection. Wild-type Sb is generally recognized as safe (GRAS) and persists in conventionally raised mice for up to 24 h, antibiotic-treated mice for up to 10 days, and in humans for approximately one week. Recently, a suite of genetic engineering tools for Sb have been developed, including transformation methods, constitutive promoters, genome editing protocols, genomic integration sites, G protein-coupled receptors, and secretion-enhancing gene knockouts. , …”
Section: Introductionmentioning
confidence: 99%
“…This is because a high-quality genome, gene regulatory data, species-specific DNA parts for genetic manipulation, and efficient transformation procedures are often missing. The process of developing these elements, termed "onboarding," can be accelerated for nonconventional ascomycete yeasts closely related to S. cerevisiae because the genomics and genetics are similar, permitting transfer of similar promoter and plasmid designs (Durmusoglu et al 2023).…”
Section: Introductionmentioning
confidence: 99%